60 GHz Substrate-Integrated Waveguide-Based Monopulse Slot Antenna Arrays - Zhu, Jianfeng; Liao, Shaowei; Li, Shufang; Xue, Quan (IEEE transactions on antennas and propagation, 2018)
This communication presents a new kind of substrate-integrated waveguide (SIW) slot antenna array with 1-D and 2-D monopulse radiation patterns. First, a new SIW magic-tee is developed, which exhibits a wide phase/amplitude balance bandwidth. Then, the magic-tee is extended to a new comparator which is used to feed the antenna with 2-D monopulse radiation pattern. Based on the proposed magic-tee and the comparator, 1-D and 2-D monopulse slot antenna arrays with 4× 4 elements are designed and measured, respectively. The experimental results show that the arrays exhibit good monopulse performance. More importantly, compared with their former counterparts, the monopulse performance of the arrays exhibits merely slight degradation over a much wider bandwidth due to the wide phase/ amplitude balance bandwidth that the comparators achieved.